War in Ukraine: an overview of environmental impacts and consequences for human health - Leal Filho, Walter; Eustachio, Joao Henrique Paulino Pires; Fedoruk, Mariia; Lisovska, Tetiana (Frontiers in Sustainable Resource Management, 2024)
This paper discusses the significant yet often neglected environmental repercussions of the Russian invasion of Ukraine, highlighting the adverse effects on soil, air, water, and biodiversity. Through a comprehensive bibliometric analysis, it examined existing research on the environmental impact of wars, focusing on key dimensions such as water, air, soil, and biodiversity. The study further explores various methods as well as sustainable-oriented solutions aimed at mitigating these effects on the environment. Furthermore, it discusses the immediate and long-term challenges Ukraine faces in its recovery efforts, emphasizing the need for environmentally conscious approaches to address the many environmental problems caused by the war issues. In the end, the paper presents findings from a workshop involving 15 Ukrainian experts from three different Ukrainian universities, which aimed to understand the broader implications of environmental damages to human health. This interdisciplinary approach offers valuable insights into the intersection of environmental degradation and public health, proposing operational strategies for recovery and sustainability in post-conflict settings.